Variation in Leaf Traits of 34 Trees and Shrubs in Summer Season in Linares, North-Eastern Mexico - Rodriguez, Humberto Gonzalez; Maiti, Ratikanta; Duenas Tijerina, Haydee Alejandra; Linan Gonzalez, Mayela Isabel; Gonzalez Diaz, Jeff Christofher; Kumari, Aruna (International Journal of Bio-resource and Stress Management, 2023)
The study undertaken in 34 species of trees and shrubs in the municipality of Linares, Nuevo Leon in Forest Faculty of Universidad Autonoma de Nuevo Leon for seasonal variations in leaf traits has revealed that there exists large variations in leaf area (cm2), specific leaf area (cm2 g-1) and leaf dry mass (g), petiole length and moisture content both in Winter and Summer seasons. Leaf area (cm2) ranged from 0.733 to 215.926 (cm2), leaf dry mass from 0.006 to 1.463 (g), specific leaf area from 11.833 to 1982.780 (cm2), leaf length from 0.700 to 51.00 (cm), leaf breadth from 0.400 to 22.400 (cm) and petiole length from 0.100 to13.00 (cm). Leaf area showed highly significant positive correlations with leaf dry weight (g) (r=0.94), leaf length (r=0.88), leaf breath (r=0.807), and petiole length (r=0.71) while the leaf dry weight showed highly significant correlation with leaf length (r=0.88), leaf breadth (r=0.775), and petiole length (r=0.734). Specific leaf area did not show any significant correlations with any of the variables studied. Therefore, leaf area, leaf length, petiole length has significant roles in plant productivity and reveals that there exists interspecific diversity among distict leaf characteristics which in turn determine distinct functional trends among the community studied.